Teachers’ Perception Related to the Implementation of Curriculum 2013 - Mitra, Delsi; Purnawarman, Pupung (Curriculum and Educational Technology Department, 2019)
The curriculum 2013 is the latest Indonesia curriculum that requires students to have 4 C?s learning (Critical thinking, Collaboration, Creativity and Communica-tion) as demanding of 21st century need. Especially for vocational school students, they have to be mastered in English as one of requirement for them to be involved in workforce. In the curriculum 2013 includes three main aspects that need to be measured; the implementation of core competence, the implementation the process of teaching and learning process and the implementation of assessment process. This study employed open-ended and close-ended questionnaires that analyzed statistically and descriptively. The finding of this study revealed the three aspects of the curriculum 2013 is well implemented yet the training and teacher development program are needed for the teachers to master the whole aspects this curriculum. Further, any attention from the students to the demands of this curriculum is also needed. Thus, it is recommended an effective and efficient trainings or in-house training of the 2013 curriculum for English teachers. Abstrak Kurikulum 2013 merupakan kurikulum nasional terbaru di Indonesia yang menuntut siswa untuk menguasai empat kecakapan Abad 21, yaitu berpikir kritis, kolaborasi, kreativitas, dan komunikasi. Terutama bagi sekolah kejuruan, siswa harus menguasai Bahasa Inggris sebagai salah satu tuntutan dunia kerja. Dalam Kurikulum 2013 terdapat tiga aspek yang perlu diukur, yaitu (1) implementasi kompetensi inti, (2) implementasi proses pengajaran dan pembelajaran, dan (3) implementasi proses penilaian hasil belajar. Penelitian ini menggunakan kuesioner terbuka dan tertutup yang hasilnya kemudian dianalisis menggunakan statistic deskriptif. Penelitian ini menemukan bahwa tiga aspek dari Kurikulum 2013 telah diterapkan dengan baik, namun tetap memerlukan program pelatihan dan pengembangan guru untuk menguasai keseluruhan aspek kurikulum. Kedepannya, perhatian dari siswa terhadap tuntutan dari kurikulum ini juga diperlukan. Oleh karena itu, in-house training Kurikulum 2013 yang efektif dan efisien direkomendasikan untuk guru Bahasa Inggris. Keywords: core competence English teacher; perception; the 2013 curriculum; vocational school